Neodymium isotope ratio measurements by CE-MC-ICPMS: investigation of isotopic fractionation and evaluation of analytical performances. Issue 11 (4th October 2017) - Martelat, Benoît; Vio, Laurent; Isnard, Hélène; Simonnet, Jérôme; Cornet, Térence; Nonell, Anthony; Chartier, Frédéric
Abstract : This study demonstrated the feasibility of precise online measurements of Nd isotope ratios by EC-MC-ICPMS. Abstract : Precise isotope ratio measurements in the nuclear field often require hyphenation of separation techniques with multicollector inductively coupled plasma mass spectrometry (MC-ICPMS). Among these separation techniques, electrokinetic methods are very interesting as they use the lowest sample volumes and produce the least amount of radioactive waste. The objectives of this study were to evaluate the performances when coupling electrokinetic techniques with MC-ICPMS for measuring isotope ratios of Nd, an element of interest for nuclear purposes. During data acquisition along the elution peak, an isotope ratio drift was observed and studied. In order to discriminate the drift induced by the MC-ICPMS detectors, the raw data of the isotope signals were corrected by taking into account the difference of time response of the Faraday cup amplifiers. An isotopic mass-dependent fractionation induced by the electrokinetic separation was then highlighted. Some of the parameters were modified ( i.e., the length of the capillary and the external pressure) to evaluate their impact on the amplitude of fractionation. Finally, the measurement performances were evaluated for all the isotope ratios. The reproducibility obtained was lower than 0.2‰ regardless of the considered Nd isotope ratio with only 0.5 ng of injected Nd.